The application of the improved chaos algorithm in the football performance prediction - Song, Hui (RISTI : Revista Ibérica de Sistemas e Tecnologias de Informação, 2016)
With the continuous progress of the science, the physical training is also gradually scientific. As a kind of important football phenomenon and rule, the statistics and the quantitative analysis method in the football field will be paid more and more attention by people. During the training process, using the scientific methods to predict the football performance can find out the game rules of the players and make the training plans. In this paper, we use the chaos prediction method to predict the football performance. In order to improve the performance of the algorithm, we improve the traditional chaos prediction algorithm and propose the improved chaos algorithm. According to the examples, we analyse the accuracy of the prediction. Keywords: Improved Chaos Algorithm, Football Performance Prediction